2013
DOI: 10.1673/031.013.13401
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Responses to Sex Pheromone of the Fall Armyworm,Spodoptera frugiperda

Abstract: Trifluoromethyl ketones reversibly inhibit pheromone-degrading esterases in insect olfactory tissues, affecting pheromone detection and behavior of moth males. In this work, (Z)-9-tetradecenyl trifluoromethyl ketone (Z9-14:TFMK), a closely-related analogue of the pheromone of the fall armyworm, Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae), was prepared and tested in electroantennogram and field tests as possible inhibitors of the pheromone action. The electroantennogram parameters, amplitude, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Larvae of S. frugiperda and H. zea were commercially acquired (Benzon Research Inc., Carlisle, PA) and held on corresponding artificial diets developed by USDA, Stoneville, MS. The temporary colonies of each species were maintained in the laboratory (27 C and a photoperiod of16:8 [L:D] h; Horner et al 2003, Malo et al 2013, enabling a supply of larvae for the laboratory and field experiments.…”
Section: Lepidoptera Stock Colonymentioning
confidence: 99%
“…Larvae of S. frugiperda and H. zea were commercially acquired (Benzon Research Inc., Carlisle, PA) and held on corresponding artificial diets developed by USDA, Stoneville, MS. The temporary colonies of each species were maintained in the laboratory (27 C and a photoperiod of16:8 [L:D] h; Horner et al 2003, Malo et al 2013, enabling a supply of larvae for the laboratory and field experiments.…”
Section: Lepidoptera Stock Colonymentioning
confidence: 99%
“…Among the structural analogs, methyl ketones (MKs) and, particularly, trifl uoromethyl ketones (TFMKs), in which the acetate group has been replaced by CH 3 CO or CF 3 CO, respectively, are good disruptants of pheromone perception in a number of lepidopteran species, such as Spodo ptera littoralis Boisduval (Duran et al, 1993;Rosell et al, 1996), Plutella xylostella (L.) (Prestwich & Streinz, 1988), Thaumetopoea pityocampa Denis & Schiffermüller (Parrilla & Guerrero, 1994), Sesamia nonagrioides (Lefevbre) (Bau et al, 1999;Riba et al, 2001), Mamestra brassicae (L.) (Renou et al, 1997), Ostrinia nubilalis (Hübner) (Riba et al, 2005), Bombyx mori (L.) (Pophof et al, 2000), Antheraea polyphemus (Cramer) (Vogt et al, 1985), Cydia pomonella (L.) (Giner et al, 2009), Zeuzera pyrina (L.) (Muñoz et al, 2011), Spodoptera frugiperda Smith (Malo et al, 2013) and Tuta absoluta (Meyrick) (Dominguez et al, 2016). In the fi eld, these chemicals induce a signifi cant Plant volatiles challenge inhibition by structural analogs of the sex pheromone in Lobesia botrana (Lepidoptera: Tortricidae) INTRODUCTION Pheromones are an important element in integrated pest management (IPM) programs, where many insect pests are successfully monitored and controlled by mass trapping and/or mating disruption (Witzgall et al, 2010).…”
mentioning
confidence: 99%
“…In summary, it shows apparent bias towards the H. ammodendron, the more vigorously branches of H. ammodendron provides T. dubia with more sufficient nutrients for growth and development. From another point of view, many studies have indicated that the antennal receptors (Malo et al, 2004(Malo et al, , 2013, olfactory system and chemosensory genes are the keys to their feeding preference (Qiu et al, 2020). Plant volatiles were responsible for the attraction of T. dubia, structure of antenna receptor, related genes and changes in enzyme activity will be further studied for the comprehensive management of them.…”
Section: Discussionmentioning
confidence: 99%